Spin-oﬀ Policy on Islamic Insurance Industry Development in Indonesia: Maslahah Perspective - Agus Waluyo (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to describe the eﬀorts to develop the sharia insurance industry in Indonesia. This study is a literature review supported by data and analysis with sources in the form of books, articles, websites and documents. This study resulted in several ﬁndings, including one of the eﬀorts to develop the sharia insurance industry was pursued by the government through a spin-oﬀ policy. The spin-oﬀ policy normatively and substantially can encourage the growth of Islamic insurance in the country and in accordance with the community expectations in actualizing beneﬁts in order to protect religion, life, descent, reason and property. The sharia insurance spin-oﬀ process in Indonesia has not run as expected. To support the acceleration of spin-oﬀ policy realization, it must be supported by strengthening regulations and human resources, product innovation, literacy, and expanding access. The implication ofthis study is that there is still a need to strengthen regulations and human resources so that the sharia insurance spin-oﬀ policy program can be realized.